Fear of the dark? Contrasting impacts of humans versus lynx on diel activity of roe deer across Europe. Issue 1 (26th December 2019) - Bonnot, Nadège C.; Couriot, Ophélie; Berger, Anne; Cagnacci, Francesca; Ciuti, Simone; De Groeve, Johannes E.; Gehr, Benedikt; Heurich, Marco; Kjellander, Petter; Kröschel, Max; Morellet, Nicolas; Sönnichsen, Leif; et al.
Abstract: Humans, as super predators, can have strong effects on wildlife behaviour, including profound modifications of diel activity patterns. Subsequent to the return of large carnivores to human‐modified ecosystems, many prey species have adjusted their spatial behaviour to the contrasting landscapes of fear generated by both their natural predators and anthropogenic pressures. The effects of predation risk on temporal shifts in diel activity of prey, however, remain largely unexplored in human‐dominated landscapes. We investigated the influence of the density of lynx Lynx lynx, a nocturnal predator, on the diel activity patterns of their main prey, the roe deer Capreolus capreolus, across a gradient of human disturbance and hunting at the European scale. Based on 11 million activity records from 431 individually GPS‐monitored roe deer in 12 populations within the EURODEER network (http://eurodeer.org ), we investigated how lynx predation risk in combination with both lethal and non‐lethal human activities affected the diurnality of deer. We demonstrated marked plasticity in roe deer diel activity patterns in response to spatio‐temporal variations in risk, mostly due to human activities. In particular, roe deer decreased their level of diurnality by a factor of 1.37 when the background level of general human disturbance was high. Hunting exacerbated this effect, as during the hunting season deer switched most of their activity to night‐time and, to a lesser extent, to dawn, although this pattern varied noticeably in relation to lynx density. Indeed, in the presence of lynx, their main natural predator, roe deer were relatively more diurnal. Overall, our results revealed a strong influence of human activities and the presence of lynx on diel shifts in roe deer activity. In the context of the recovery of large carnivores across Europe, we provide important insights about the effects of predators on the behavioural responses of their prey in human‐dominated ecosystems. Modifications in the temporal partitioning of ungulate activity as a response to human activities may facilitate human–wildlife coexistence, but likely also have knock‐on effects for predator–prey interactions, with cascading effects on ecosystem functioning. Abstract : The authors compared diel activity of roe deer across 12 European populations. Deer were more nocturnal when human disturbance was high, but more diurnal in the presence of lynx, their main natural predator. Modifications in the temporal partitioning of ungulate activity likely have knock‐on effects for a variety of ecological processes. Photo credit: Nicolas Cèbe (CEFS‐INRA). Translated Abstract: Résumé Les humains, en tant que 'super‐prédateurs', peuvent avoir des effets importants sur le comportement de la faune sauvage, y compris des modifications profondes de leurs rythmes circadiens d'activité. A la suite du retour des grands carnivores dans les écosystèmes anthropisés, de nombreuses espèces proies ont ajusté leur comportement spatial à ces paysages de la peur contrastés, générés à la fois par les pressions liées aux risques anthropiques et à la présence de leurs prédateurs naturels. Les effets du risque de prédation sur les modifications temporelles des rythmes circadiens d'activité des proies restent cependant largement inconnus dans les écosystèmes dominés par l'homme. Ici, nous avons étudié l'influence de la densité de lynx Lynx lynx, un prédateur nocturne, sur les rythmes circadiens d'activité de leur proie principale, le chevreuil Capreolus capreolus, à travers un gradient de pressions anthropiques à l'échelle Européenne. Sur la base de plus de 11 million de données d'activité issues de 431 suivis individuels de chevreuils équipés de colliers GPS provenant de 12 populations au sein du réseau EURODEER (http://eurodeer.org ), nous avons analysé comment le risque de prédation par le lynx, associé aux risques létaux et non‐létaux des activités humaines, influence la diurnalité des chevreuils. Nous avons démontré une forte plasticité des rythmes circadiens d'activité des chevreuils en réponse aux variations spatio‐temporelles du risque, et notamment face aux activités humaines. Plus particulièrement, les chevreuils diminuent leur degré de diurnalité d'un facteur de 1.37 lorsque le dérangement humain est important. La chasse accentue cet effet, puisque durant la saison de chasse les chevreuils basculent la plupart de leur activité de nuit, et dans une moindre mesure, durant l'aube également, bien que ce patron soit essentiellement variable en fonction de la densité de lynx. En effet, en présence de lynx, leur principal prédateur, les chevreuils sont relativement plus diurnes. Globalement, nos résultats révèlent une forte influence des activités humaines et de la présence de lynx sur l'ajustement des rythmes circadiens d'activité des chevreuils. Dans le contexte du retour des grands carnivores en Europe, notre étude apporte de nouvelles connaissances sur les effets des prédateurs sur la réponse comportementale de leur proie dans des écosystèmes anthropisés. La modification de la répartition temporelle de l'activité des ongulés en réponse aux activités humaines pourrait être un facteur facilitant la coexistence homme‐faune sauvage, avec toutefois des conséquences autres sur les interactions prédateurs‐proies et leurs effets en cascade sur le fonctionnement des écosystèmes.